Pengaruh Lingkungan, Motivasi, dan Stres Kerja Terhadap Kinerja Karyawan UMKM Gundaling Uis - Nadeak, Penita Irmasari; Saragih, Lenny Menara Sari; Amadi, Jam an (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the impact of the Work Environment, Motivation, and Work Stress on the level of Employee Performance at Gundaling Uis MSME. Methodologically, a quantitative descriptive approach was adopted by applying multiple linear regression analysis using SPSS 25 software to empirically test the research model. The population in this study consisted of all employees of Gundaling Uis MSME; therefore, a saturated sampling technique was employed, involving 45 respondents as the sample. Primary data were collected online using a questionnaire instrument based on Google Forms. The results of the data analysis reveal that, both partially and simultaneously, the variables of Work Environment, Motivation, and Work Stress have a significant effect on Employee Performance.